Plasma polyunsaturated fatty acid concentrations and sleep apnea risk: A two-sample Mendelian randomization study - Wang, Jiao; Huang, Yingyue; Yang, Huiling; Lin, Zihong; Campos, Adrian I.; Rentería, Miguel E.; Xu, Lin (Frontiers in Nutrition, 2022)
Background: Previous observational studies have found that lower levels of circulating polyunsaturated fatty acids (PUFAs) were associated with a higher risk of sleep apnea (SA). However, the causality of the association remains unclear. Methods: We used the two-sample Mendelian randomization (MR) study to assess the causal association of omega-3 and omega-6 fatty acids with SA. Single-nucleotide polymorphisms (SNPs) predicting the plasma level of PUFAs at the suggestive genome-wide significance level (p <5× 10−6) were selected as instrumental variables from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) (n=~8,000) Consortium. For outcomes, summary-level statistics of SA were obtained from the latest genome-wide association study, which combined five cohorts with a total number of 25,008 SA cases, 172,050 snoring cases (total = 523,366). Results: We found no association of α-linolenic acid (odds ratio (OR)=1.09 per % changed, 95% confidence interval (CI) 0.67-1.78), eicosapentaenoic acid (OR=0.94, 95% CI 0.88-1.01), docosapentaenoic acid (OR=0.95, 95% CI 0.88-1.02) and docosahexaenoic acid (OR=0.99, 95% CI 0.96-1.02) with the risk of SA using inverse-variance weighted (IVW) method. Moreover, for omega-6 PUFAs, no association of linoleic acid (OR=0.98, 95% CI 0.96-1.01), arachidonic acid (1.00, 95% CI 0.99-1.01) and adrenic acid (0.93, 95% CI 0.71-1.21) with the risk of SA was found. Similar no associations of PUFAs with SA was found in single-locus MR analysis. Conclusion: In the current study, we first found that no genetic evidence to support the causal role of omega-3 and omega-6 PUFAs in the risk of SA. From a public health perspective, our findings refute the notion that consumption of foods rich in PUFAs or the use of PUFAs supplementation can reduce the risk of SA.